Production of muons from heavy flavor decays at forward rapidity in pp and Pb-pb collisions at √sNN=2.76 TeV - Abelev, Betty; Busch, Oliver; Engel, Heiko; Glässel, Peter; Grajcarek, Robert; Herrmann, Norbert; Krawutschke, Tobias; Kweon, MinJung; Lara Martinez, Camilo Ernesto; Lohner, Daniel; Mercado Pérez, Jorge; Oyama, Ken; et al. (Physical review letters, 2012)
The ALICE Collaboration has measured the inclusive production of muons from heavy-flavor decays at forward rapidity, 2.5<y<4, in pp and Pb-Pb collisions at √sNN=2.76 TeV. The pt-differential inclusive cross section of muons from heavy-flavor decays in pp collisions is compared to perturbative QCD calculations. The nuclear modification factor is studied as a function of pt and collision centrality. A weak suppression is measured in peripheral collisions. In the most central collisions, a suppression of a factor of about 3-4 is observed in 6<pt<10 GeV/c. The suppression shows no significant pt dependence.
Im Titel steht der Ausdruck "sNN" unter dem Wurzelsymbol, "NN" ist dabei tiefgestellt
B. Abelev, O. Busch, H. Engel, P. Glässel, R. Grajcarek, N. Herrmann, T. Krawutschke, M.J. Kweon, C. Lara, D. Lohner, J. Mercado Pérez, K. Oyama, Y. Pachmayer, K. Reygers, R. Schicker, K. Schweda, J. Stachel, J. Ulrich, J. Wiechula, V. Winbelband, P. Zelnicek, A. Zimmermann [und weitere]
Gesehen am 30.11.2018